HACCP System Design and GMP/SSOP Evaluation for Meatball Production: A Case Study at Bakso Solo Jatimulyo - Kamelia Zuchri Bukit; Untung Trimo Laksono; Deni Subara (Journal of Agritechnology and Food Processing, 2025)
This study assesses GMP and SSOP compliance and develops a HACCP plan based on SNI 01-4852-1998 for meatball production at Bakso Solo Jatimulyo. Using a descriptive qualitative approach, we evaluated the implementation of Good Manufacturing Practices (GMP) and Sanitation Standard Operating Procedures (SSOP). The facility scored 82% for GMP compliance but only 49.1% for SSOP implementation. Furthermore, the study identified primary biological, chemical, and physical hazards requiring control. Consequently, operators should monitor all production activities, specifically the cooking stage, which serves as a Critical Control Point (CCP).Keywords: critical control point; GMP; HACCP; Meatball